2021
DOI: 10.1111/cid.12996
|View full text |Cite
|
Sign up to set email alerts
|

The role of cortical perforations in allogeneic block grafting for lateral augmentation in maxilla: A randomized clinical trial

Abstract: Background The need of decortication on the recipient site remains unclear for bone regeneration. To our knowledge, there are no human clinical trials that studied the influence of decortication on cancellous allogeneic block grafting. Purpose The aim of the present study is to evaluate the influence of perforating the cortex of the recipient site on cancellous allogeneic block graft integration and revascularization in the maxilla. Material and Methods Twenty‐six patients referred for lateral bone augmentatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
(111 reference statements)
1
2
0
Order By: Relevance
“…Apart from the fit of the graft, the defect site preparation might have an influence on the integration and vascularization of the block graft. Tresguerres and coworkers showed that cortical perforation of the recipient site did not influence the angiogenesis and new bone formation compared to nonperforated sites [40]. In this presented case report, there was uneventful healing, resulting in minimal to no volume loss of the customized allograft bone block 5 months after placement, and the histology after 6 months showed 46.61% mineralized bone, similar to the previous published results [40].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Apart from the fit of the graft, the defect site preparation might have an influence on the integration and vascularization of the block graft. Tresguerres and coworkers showed that cortical perforation of the recipient site did not influence the angiogenesis and new bone formation compared to nonperforated sites [40]. In this presented case report, there was uneventful healing, resulting in minimal to no volume loss of the customized allograft bone block 5 months after placement, and the histology after 6 months showed 46.61% mineralized bone, similar to the previous published results [40].…”
Section: Discussionsupporting
confidence: 88%
“…Tresguerres and coworkers showed that cortical perforation of the recipient site did not influence the angiogenesis and new bone formation compared to nonperforated sites [40]. In this presented case report, there was uneventful healing, resulting in minimal to no volume loss of the customized allograft bone block 5 months after placement, and the histology after 6 months showed 46.61% mineralized bone, similar to the previous published results [40]. After three months of healing, the implant stability showed ISQ values over 70.…”
Section: Discussionmentioning
confidence: 99%
“…The defect was cleaned from connective tissue residues without decortication of the local bone and the defect size was measured with a sterile caliper. In this context, there is no evidence according decortication benefits [ 41 , 42 ]. Then, CP were adjusted and trimmed to the correct size by a cutting disc after rehydration in 0.9% saline at room temperature for at least 10 min to increase CP breaking strength and flexibility [ 35 ].…”
Section: Methodsmentioning
confidence: 99%